Analyzing Figurative Language in Taylor Swift’s Selected Songs: A Qualitative Study - Amalia MN, Ade Rezky (English Literature Studi Program Universitas Islam Makassar, 2024)
This study explores the use of figurative language in selected songs by Taylor Swift to understand its prevalence and impact. The primary objectives are to identify the types of figurative language used and determine the most dominant form. Employing a qualitative approach, this research analyzes five songs: